Identifikasi Prediksi Kejadian Incident Pada Area Produksi Fabrikasi Drum, Filling Point, dan Distribusi PT X di Lingkungan Bitument Plant Gresik - Astriningrum Titipangesti Kusumarini; Abdul Rohim Tualeka; Meirina Ernawati; Shintia Yunita Arini; Rizaldi Nanda Pratama (Universitas Malahayati Lampung, 2023)
ABSTRACT The rapid development of the asphalt industry forces asphalt industry companies to continuously develop and innovate. Companies that are able to develop and innovate will certainly always increase their advantage in competition in the industrial world. This can be achieved if the company has a quality product. In improving product quality, there are potential hazards in the workplace such as incidents. This study aims to identify the prediction of incident events in the production area of drum fabrication, filling points, and distribution of PT X in the gresik bitument plant environment in 2023. This research is a cross-sectional research based on the time of study. The completion time of this research is 3 months. Data analysis techniques in this study start from hazard identification, potential hazard assessment, and hazard control. In the production process of making ready drums to the asphalt loading process in drums in the distribution there is a near miss that can cause incidents in every production machine. The most incidents are the occurrence of being scratched by sheets, stuck to pinched in the distribution load area for workers. In addition, there is also a high engine sound that causes noise and chemical factors in painting booth machines and filling in drums can cause interference with the respiratory system in the long run. There is a prediction of the occurrence of incidents in every production machine. The most incidents are the occurrence of sheet scratches on workers, mired in sandwiches between drums in the distribution loading area for workers. It is necessary to improve the implementation of the Risk Control Hierarchy, starting from Elimination, Substitution, Design/Modification, Administration and Personal Protective Equipment (PPE). Keywords: Hazard, Risk, Incident, Control ABSTRAK Pesatnya perkembangan industry aspal memaksa perusahaan industry aspal untuk terus menerus dalam berkembang dan berinovasi. Perusahaan yang mampu berkembang dan berinovasi tentunya akan senantiasa meningkatkan keunggulan dalam persaingan di dunia industri. Hal ini dapat dicapai apabila perusahaan memiliki produk yang berkualitas. Dalam meningkatkan kualitas produk terdapat potensi bahaya di tempat kerja seperti kejadian incident. Penelitian ini bertujuan untuk mengidentifikasi prediksi kejadian incident pada area produksi fabrikasi drum, filling point, dan distribusi PT X di lingkungan bitument plant gresik tahun 2023. Penelitian ini bersifat cross sectional dilihat berdasarkan waktu penelitian. Waktu penyelesaian penelitian ini 3 bulan. Teknik analisis data dalam penelitian ini dimulai dari identifikasi bahaya, penilaian potensi bahaya, dan pengendalian bahaya. Pada proses produksi pembuatan ready drum hingga proses muat aspal in drum di distribusi terdapat near miss yang mampu mengakibatkan incident di setiap mesin produksi. Incident terbanyak yaitu kejadian tergores oleh sheet, kejeglong hingga terjepit di area muat distribusi pada pekerja. Selain itu juga terdapat suara mesin yang tinggi hingga menyebabkan kebisingan dan faktor kimia pada mesin painting booth dan filling in drum dapat mengakibatkan gangguan pada system pernafasan dalam jangka panjang. terdapat prediksi terjadinya incident di setiap mesin produksi. Incident terbanyak yaitu kejadian tergores sheet pada pekerja, terperosok hingga terjepit pada sela sela drum di area muat distribusi pada pekerja. Perlunya ditingkatkan penerapan Hierarki Pengendalian Risiko yaitu mulai dari Eliminasi, Substitusi, Perancangan/Modifikasi, Administrasi dan Alat Pelindung Diri (APD). Kata Kunci: Bahaya, Risiko, Incident, Pengendalian.